A Novel Method of Newborn Chest Compression: A Randomized Crossover Simulation Study - Smereka, Jacek; Szarpak, Lukasz; Ladny, Jerzy R.; Rodriguez-Nunez, Antonio; Ruetzler, Kurt (Frontiers in Pediatrics, 2018)
Objective. To compare a novel two-thumb chest compression technique with standard techniques during newborn resuscitation performed by novice physicians in terms of median depth of chest compressions, degree of full chest recoil, and effective compression efficacy. Patients and Methods. The total of 74 novice physicians with less than 1-year work experience participated in the study. They performed chest compressions using three techniques: (A) The new two-thumb technique (nTTT). The novel method of chest compressions in an infant consists in using two thumbs directed at the angle of 90 degrees to the chest while closing the fingers of both hands in a fist. (B) TFT. With this method, the rescuer compresses the sternum with the tips of two fingers. (C) TTHT. Two thumbs are placed over the lower third of the sternum, with the fingers encircling the torso and supporting the back. Results. The median depth of chest compressions for nTTT was 3.8 (IQR, 3.7–3.9) cm, for TFT – 2.1 (IQR, 1.7–2.5) cm, while for TTHT – 3.6 (IQR, 3.5–3.8) cm. There was a significant difference between nTTT and TFT, and TTHT and TFT (p < 0.001) for each time interval during resuscitation. The degree of full chest recoil was 93% (IQR, 91–97) for nTTT, 99% (IQR, 96–100) for TFT, and 90% (IQR, 74–91) for TTHT. There was a statistically significant difference in the degree of complete chest relaxation between nTTT and TFT (p < 0.001), between nTTT and TTHT (p = 0.016), and between TFT and TTHT (p < 0.001). Conclusion. The median chest compression depth for nTTT and TTHT is significantly higher than that for TFT. The degree of full chest recoil was highest for TFT, then for nTTT and TTHT. The effective compression efficiency with nTTT was higher than for TTHT and TFT. Our novel newborn chest compression method in this manikin study provided adequate chest compression depth and degree of full chest recoil, as well as very good effective compression efficiency. Further clinical studies are necessary to confirm these initial results. Keywords: chest compression; technique; cardiopulmonary resuscitation; newborn; physicians.